2015
DOI: 10.1186/s12885-015-1817-5
|View full text |Cite
|
Sign up to set email alerts
|

KIT exon 10 variant (c.1621 A > C) single nucleotide polymorphism as predictor of GIST patient outcome

Abstract: BackgroundTumor genotype plays a crucial role in clinical management of GIST. Whether genetic polymorphism of KIT may influence GIST patient outcome is unclear.MethodsWe investigated the biological and clinical significance of the presence of KIT exon 10 variant (c.1621 A > C), KITL541, in a transfected cell line (3 T3 L541) and in two retrospectively collected series of 109 GIST patients in total. The control group consisted of 60 healthy donors collected at the French department of blood transfusion.ResultsI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…All of the TP53 mutations in the organoid cultures were homozygous (> 0.9 allele frequency), yet diverse with respect to mutation type (missense, nonsense, frame‐shift, or splice variant mutations). In addition to somatic mutations with proven tumorigenic potential, a number of known variant alleles were identified, including ROCK2 (c.1292C>A), KIT (c.1621A>C), MLH1 (c.655A>G), and MSH6 (c.472C>T) which could potentially influence the malignant phenotype (Kalender et al , ; Nakamura et al , ; Brahmi et al , ). Apart from TP53 , MLH1, and MSH6 , we also found point mutations in other genes with functions in DNA repair and chromosome stability, including ATM (c.4534G>A), ATR (c.1517A>G), BRIP1 (c.254T>A), and FANCA (c.1238G>T).…”
Section: Resultsmentioning
confidence: 99%
“…All of the TP53 mutations in the organoid cultures were homozygous (> 0.9 allele frequency), yet diverse with respect to mutation type (missense, nonsense, frame‐shift, or splice variant mutations). In addition to somatic mutations with proven tumorigenic potential, a number of known variant alleles were identified, including ROCK2 (c.1292C>A), KIT (c.1621A>C), MLH1 (c.655A>G), and MSH6 (c.472C>T) which could potentially influence the malignant phenotype (Kalender et al , ; Nakamura et al , ; Brahmi et al , ). Apart from TP53 , MLH1, and MSH6 , we also found point mutations in other genes with functions in DNA repair and chromosome stability, including ATM (c.4534G>A), ATR (c.1517A>G), BRIP1 (c.254T>A), and FANCA (c.1238G>T).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the germline KIT p.(Met541Leu) variant was found in 9% of TETs. To date, Met541Leu has mostly been reported in GISTs, in which it is associated with an increased risk of tumour progression and dissemination [ 81 , 82 , 83 ]. Using transfected cell lines, Brahmi et al found that KIT p.(Met541Leu) induced mutant-like intracellular signalling in the presence of stem cell factor [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…M541L is the most common KIT polymorphism known (rs3822214) with a minor allele frequency of 0.08 in the gnomAD database ( https://gnomad.broadinstitute.org/ ), is classified as benign/likely benign on ClinVar ( www.ncbi.nlm.nih.gov/clinvar/ ), and has been described in the literature as a driver of pediatric mastocytosis [ 25 ]. In patients with GIST, the KIT M541L polymorphism has been shown to be associated with a higher risk of metastasis at diagnosis, and with a higher risk of relapse [ 26 , 27 ]. A higher prevalence of this genotype has also been seen in the disease of higher-risk patients (with tumor duality, un-resectable and/or locally advanced disease, in addition to metastases at diagnosis) compared with patients with localized GIST [ 27 ].…”
Section: Resultsmentioning
confidence: 99%